2009
DOI: 10.1111/j.1582-4934.2008.00517.x
|View full text |Cite
|
Sign up to set email alerts
|

HER‐2 overexpression/amplification in Barrett’s oesophagus predicts early transition from dysplasia to adenocarcinoma: a clinico‐pathologic study

Abstract: Barrett’s oesophagus (BO) is the primary precursor lesion for oesophageal adenocarcinoma (ADC). The natural history of metaplasia-dysplasia-carcinoma sequence remains largely unknown. HER2/neu oncogene results overexpressed/amplified in preneoplastic lesions and in ADC of the oesophagus and it has been associated with poor prognosis. Our aim was to evaluate the role of HER2 overexpression/amplification in predicting the conversion from precursor lesions to ADC. We retrospectively evaluated by univariate analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 45 publications
1
34
1
Order By: Relevance
“…Previous studies of RTK expression in Barrett’s esophagus have been limited to an assessment of HER2, which is overexpressed in a minority of cases [35]. HER2 overexpression in this study was present in 3.4% of biopsy specimens, lower than the rate of HER1 or HER3 overexpression.…”
Section: Discussioncontrasting
confidence: 53%
“…Previous studies of RTK expression in Barrett’s esophagus have been limited to an assessment of HER2, which is overexpressed in a minority of cases [35]. HER2 overexpression in this study was present in 3.4% of biopsy specimens, lower than the rate of HER1 or HER3 overexpression.…”
Section: Discussioncontrasting
confidence: 53%
“…Four studies were population-based (median follow-up, 5.0 years), 2,3,9,21 4 were multicenter studies (median follow-up, 4.7 years), 27,29,39,42 and the remaining were single-center studies (median follow-up, 4.8 years). 19,20,2226,28,3038,40,41 Most studies reported or permitted a missed vs incident cutoff of exactly 12 months to be applied, with the exception of 2 studies reporting cutoffs of 9 and 6 months, 32,39 and 1 study for which only a cutoff of 14 months could be applied. 24 In these 3 studies, EAC (and HGD-EAC) detected before and after their respective cutoffs were classified as missed and incident, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…38 The prevalence of HER2 positive has been found to be 15e38% in Barrett's oesophagus by utilizing various methods including PCR, 39 FISH and IHC. 40 An Italian study suggested that the presence of HER2 amplification in dysplastic lesions was statistically related to progression (P value ¼ 0.038), 40 highlighting the likely role of HER2 in the evolution from dysplasia to adenocarcinoma of the oesophagus. Similarly, HER2 overexpression seems to predict poor survival in Barrett's oesophagus-associated adenocarcinoma (P value ¼ 0.03).…”
Section: Her2 and Premalignant Lesionsmentioning
confidence: 98%